Особенности распределения контактных давлений в сопряжении деталей с дискретным упрочнением - Шеремет, В. Н.; Веретельник, Олег Викторович; Литвин, Б. Я.; Шейко, А. И.; Кравченко, Сергей Александрович (НТУ "ХПИ", 2013)
In the paper results are described for research of features of stressed-deformed state at contact interaction of details which surfaces are discretely strengthened. The substantial irregularity of contact pressure distribution is detected on contact surface.
Keywords: состояние напряженно-деформированное; поверхность контактная; контакт деталей; упрочнение поверхности